Family therapists’ adult attachment styles and the therapeutic alliance - Yusof, Yusmarhaini; Carpenter, John (John Wiley & Sons, Inc., 2015)
Therapists’ adult attachment style may affect their ability to form effective therapeutic alliances.An analysis of semi-structured interviews with eleven family therapists explored the relationship between their adult attachment styles, as assessed using a self-report measure, and their perceptions of the therapeutic alliance. A framework analysis was employed, using four dimensions of the therapeutic alliance: engagement in the therapeutic process, emotional connection to the therapist, safety within the therapeutic system and shared sense of purpose within the family.Responses were compared between therapists with secure and insecure attachment styles according to different dimensions of the therapeutic alliance.There were no substantial differences in therapists’ accounts of their approach to engagement and creating a sense of safety; however they differed in their approaches to managing clients’ hostility.Secure and insecure therapists differed in one of the dimensions of therapeutic alliance; emotional connections to family members.Training and supervision could incorporate an understanding of attachment style. Suggestions are made for future research based on this exploratory study.